I need to show that the following formula yields a well-defined function: f: Z8 --> Z8 defined by f([x]8) = [mx]8 for any m belonging to Z.
Follow Math Help Forum on Facebook and Google+
Originally Posted by page929 I need to show that the following formula yields a well-defined function: f: Z8 --> Z8 defined by f([x]8) = [mx]8 for any m belonging to Z. $\displaystyle [x]_8=[y]_8\Longrightarrow [x-y]_8=[0]_8\Longrightarrow [m(x-y)]_8=[mx-my]_8=[0]_8\Longrightarrow [mx]_8=[my]_8$ Tonio
View Tag Cloud